The bowel cancer awareness campaign 'Be Clear on Cancer': sustained increased pressure on resources and over‐accessed by higher social grades with no increase in cancer detected. (2nd February 2016) - Hall, S. J.; Peacock, J. D. H.; Cochrane, L. A.; Peacock, O.; Tierney, G. M.; Tou, S. I. H.; Lund, J. N.
Abstract: Aim: To evaluate the impact of the national 'Be Clear on Cancer' bowel cancer reminder campaign on service and diagnosis at a single UK institution. Secondly, to evaluate the socio‐economic background of patients referred before and after the reminder campaign compared with the regional demographic. Method: Suspected cancer 2‐week wait patients in the 3 months precampaign, postcampaign and after the reminder campaign were included. Demographics, investigations and diagnosis were recorded. The postcode was used to allocate a National Readership Survey social grade. Results: Three hundred and eighty‐three referrals were received in the 3 months precampaign, 550 postcampaign and 470 postreminder campaign. There were significant increases in the monthly referral rates following the campaign ( P  <   0.001 in both the post‐ and postreminder periods). Significantly more patients from social grades AB and C1C2 than expected from regional demographics were referred precampaign and after the reminder campaign ( P  <   0.001 in each case). There were no significant differences between the proportions of patients diagnosed with colorectal cancer in the three study periods ( P  =   0.710). Conclusion: The 'Be Clear on Cancer' bowel cancer campaign has had a significant sustained impact on resources. It has failed to increase referrals among lower socio‐economic grades, leading to an increase in 'worried well' referrals and no change in numbers, or the stage, of colorectal cancers diagnosed.